Bringing students closer to the issues of indoor environmental quality and technology using nEMoS device: an experience in Albania - Salamone Francesco; Lorenzo Belussi; Ludovico Danza; Etleva Dobjani; Matteo Ghellere; Italo Meroni; Arben Shtylla; Saimir Shtylla (Acta Polytechnica CTU Proceedings, 2022)
The article presents the outcomes of a monitoring campaign and a survey performed in a~school building in Tirana. Included in the Bilateral Agreement between the National Research Council of Italy and the Ministry of Education and Sport of the Republic of Albania, the research is based on environmental analysis, collection of data from monitoring of environmental variables and students' feedback. The monitoring of Indoor Environmental Quality (IEQ) was carried out with a~nearable Environmental Monitoring System (nEMoS) for IEQ purposes, designed and developed by ITC-CNR based on the Do-It-Yourself (DIY) philosophy. The proliferation of the maker movement philosophy has promoted the diffusion of DIY-based technologies. The spread of this movement is observed outside schools but there is a growing interest among educators to introduce this philosophy in the students' education, approaching to STEAM (Science Technology Engineering Arts Mathematics) in a different and more stimulating way. The application of two nEMoS devices in two classrooms (in different locations) aroused the curiosity of students, bringing them closer to the world of technology with a practical example. It also increased their awareness about the overall IEQ conditions in the classrooms where they spend a considerable part of their lives.